Preparation and characterization of supported ionic liquid membrane based on PSU/BMIM BF4 for gas seperation - Gwee, Ye Zhao (2014)
The purpose of this project is to prepare polysulfone membranes by using the coagulation bath method and then proceed to find out the influence of two different types of ionic liquid on the membranes. The polymer solution was prepared by mixing 20 g of polysulfone crystals with 80 ml of NMP. To obtain the polysulfone membranes, thin layers of polysulfone solution were coated onto the carbon substrate and subsequently being put into different coagulation agents to perform wet phase inversion. The coagulation agents used were ethanol and ethylene glycol.